A relação família escola: uma análise sob o olhar do processo de ensino aprendizagem na escola EMEIF Cristo Salvador na comunidade Maúba – Abaetetuba-PA - SARGES, Fernanda Carvalho de (2019)
The act of educating has as its principle to ensure the formation and physical, intellectual and moral development of a human being. In this regard, the paper seeks to emphasize the importance of family participation in school, aiming at the formation of students. Both family institutions should pursue the same goals of making citizens responsible, ethical, critical and reflective, and therefore their plots and contributions must be meaningful for this formation. To better address this theme, the paper aims to analyze the relationship between family and school in the process of teaching and learning of students. In order to achieve this purpose,asemi-structured interview was carried out as a methodological basis at the four-month Christ Salvador Municipal Elementary and High School Interview with a teacher from a multi-grade class, a manager and five families who accepted participate in the interviews and residing in the community and where they seek to consider the teaching-learning process in relation to family and school participation taking into account the theoretical basis of Miguel Arroyo, Paulo Freire and José Carlos Libaneo, among others, in order to contribute to the community.researched. The research concludes by pointing out that family participation in school is of paramount importance in monitoring the teaching and learning process, working with the teacher and the manager and that the teacher should understand the relevance of methodologies capable of bringing motivation, interest and greater student participation in each content covered.